2017
DOI: 10.18632/oncotarget.23364
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the dysregulated inflammasome-based molecular functionome in the malignant transformation of endometriosis-associated ovarian carcinoma

Abstract: The coexistence of endometriosis (ES) with ovarian clear cell carcinoma (CCC) or endometrioid carcinoma (EC) suggested that malignant transformation of ES leads to endometriosis associated ovarian carcinoma (EAOC). However, there is still lack of an integrating data analysis of the accumulated experimental data to provide the evidence supporting the hypothesis of EAOC transformation. Herein we used a function-based analytic model with the publicly available microarray datasets to investigate the expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
(33 reference statements)
1
26
0
Order By: Relevance
“…A recent report analyzed the prevalence of cachexia in 14 different cancer types known to exhibit cachexia or a muscle wasting syndrome within the United States and the European Union, and found that over 1.3 million cancer patients exhibited clinical signs of cachexia in these oncological settings [42]. Reports have shown that cachexia is mediated, at least in part, by canonical NF-κB signaling [39, 43]. As such, a thoughtful examination of this signaling paradigm could pave the way for novel therapeutics to address this current deficit.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report analyzed the prevalence of cachexia in 14 different cancer types known to exhibit cachexia or a muscle wasting syndrome within the United States and the European Union, and found that over 1.3 million cancer patients exhibited clinical signs of cachexia in these oncological settings [42]. Reports have shown that cachexia is mediated, at least in part, by canonical NF-κB signaling [39, 43]. As such, a thoughtful examination of this signaling paradigm could pave the way for novel therapeutics to address this current deficit.…”
Section: Discussionmentioning
confidence: 99%
“…AIM2 is a member of innate immune sensors that initiate inflammasomes and trigger secretion of proinflammatory cytokines [ 66 ]. Although it has displayed both tumor suppression and promotion roles across cancer types, its upregulation in ovarian cancers suggests it could promote EOC progression [ 67 , 68 ]. STAB1 is a transmembrane receptor expressed on macrophages and lymphatic endothelial cells that acts as an inhibitor of antitumor immunity [ 69 ].…”
Section: Genetic Susceptibility Mediated By Dna Methylationmentioning
confidence: 99%
“…Further work has been done by Chang et al [41], who documented the crucial role of inflammation in the malignant transformation of endometriosis by analyzing microarray data. They observed that 7 genes of inflammasome complex ( Caspase-4 , Caspase-7 , Caspase-8 , NLRP3 , AIM2 , PYCARD , NAIP ) and 11 genes of the inflammasome-related pathway ( IL-1B , IL1RL1 , IL-18 , TLR1 , TLR7 , TOLLIP , NFKBIA , TNF , TNFAIP3 , INFGR2 , P2RX7 ) were highly expressed in endometriosis-associated ovarian carcinoma and demonstrated a tendency to correlate with poor survival.…”
Section: Genome Profile Of Endometriosis and Associated Cancermentioning
confidence: 99%